2010
DOI: 10.1002/aqc.1113
|View full text |Cite
|
Sign up to set email alerts
|

Former distribution and decline of the burbot (Lota lota) in the UK

Abstract: ABSTRACT1. Species reintroductions are an increasingly fashionable tool among conservation practitioners for restoring locally and nationally extinct populations. For a reintroduction programme to be successful, an understanding of the causes of the decline of a species is required. This, however, proves challenging when baseline data on the distribution and abundance of the species are limited.2. This paper uses evidence from historical literature to map the former distribution of the burbot (Lota lota) withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 34 publications
0
44
0
Order By: Relevance
“…In the UK, the point at which the overall Burbot population was present at half of the locations was reached around 1907, almost 50 years earlier (a & 1900;Worthington et al, 2010) than in the Netherlands. The decline of Burbot in the UK appears to have been primarily caused by the structural modification and anthropogenic pollution of rivers (Worthington et al, 2010).…”
Section: Historic Decline: Causes and Conservation Aspectsmentioning
confidence: 97%
See 4 more Smart Citations
“…In the UK, the point at which the overall Burbot population was present at half of the locations was reached around 1907, almost 50 years earlier (a & 1900;Worthington et al, 2010) than in the Netherlands. The decline of Burbot in the UK appears to have been primarily caused by the structural modification and anthropogenic pollution of rivers (Worthington et al, 2010).…”
Section: Historic Decline: Causes and Conservation Aspectsmentioning
confidence: 97%
“…Moreover, varying sources of information yield data of different quality and nature, and as a consequence, are subject to interpretive bias (Van Neer & Ervynck, 2010). Nonetheless, the quantitative analysis showed that, despite the descriptive nature of the historic data and issues mentioned above, anecdotal evidence can still provide valuable insights as to the reconstruction of historic abundance and decline of a species, emphasising the value and necessity of historical information to be taken into account when addressing conservation issues (cf Pauly, 1995;Shaffer et al, 1998;Worthington et al, 2010Worthington et al, , 2011.…”
Section: Value Of Anecdotal Evidencementioning
confidence: 98%
See 3 more Smart Citations